Prevalence of Stroke Associated Pneumonia in Stroke Patients - Husnain Hashim, Laraib Shahid, Danial Bajwa, Rashid Usman, Sabeen Saleema Ahmed, Momina Khokhar (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Stroke patients are most commonly susceptible to pulmonary infection that adversely affects the duration of hospitalization and clinical outcomes. Stroke affecting the respiratory system and causing neurological damage contributed to higher morbidity and mortality rate due to complications such as stroke-associated pneumonia (SAP). Early identification of high risk stroke patients and their management are imperative to reduce the prevalence of stroke-associated pneumonia. The present study aim was to determine the prevalence of stroke-associated pneumonia in stroke patients. Methodology: This cross-sectional descriptive case series was carried out on 226 stroke patients in the Department of Neurology, Fauji Foundation Hospital, Rawalpindi from January 2020 to December 2021. Stroke patients aged 30 to 70 years of either gender diagnosed with stroke were enrolled. Cough, fever and non-homogenous opacities observed on chest X-rays were used for the diagnosis of stroke. Patients with a history of pneumonia were excluded. Detailed history and complete examination was obtained for stroke diagnosis followed up for 1 month. SPSS version 25 was used for data analysis. Results: Of the total 226 stroke patients, there were 118 (52.2%) males and 108 (47.8%) females. The overall mean age was 48.62±8.45 years. Age-wise distribution of all patients were as follows; 72 (31.9%) 30-40 years, 106 (46.8%) 41-50 years, 32 (14.2%) 51-60 years, and 16 (7.1%) 61-70 years. The prevalence of stroke-associated pneumonia was 46 (20.4%). The incidence of diabetes mellitus, hypertension, ischemic heart disease, atrial fibrillation, congestive cardiac failure, and thrombophilia state was 48 (21.2%), 36 (15.9%), 28 (12.4%), 19 (8.4%), 14 (6.2%), and 8 (3.5%) respectively. Diabetes mellitus patients were more susceptible to stroke-associated pneumonia followed by hypertension and cardiac diseases. The incidence of stroke-associated pneumonia was 33 (14.6%) among patients having 6 to 12 hours stroke length against 13 (5.8%) with shorter duration. Conclusion: The present study found that the prevalence of stroke-associated pneumonia was 20.4% among stroke patients. Diabetes, hypertension, cardiac diseases, atrial fibrillation among stroke patients are the different risk factors that develop stroke-associated pneumonia. Early identification and better management could prevent the stroke-associated pneumonia in stroke patients. Keywords: Prevalence, Stroke-associated pneumonia, Stroke